ETABLISEMEN PELAYANAN KOMUNITAS SEL DI SEKITAR WILAYAH MEKARWANGI BANDUNG BAGI PENGEMBANGAN GEREJA - Simanjuntak, Ferry; Argareni, Kezia; Theofany, Shekinah (Publikasi dan UKI Press UKI Toraja., 2024)
Implementation of cell community pioneering activities around Mekarwangi, Bandung, utilizes diverse approaches, flexible time and different targets. The case study method is used by observing the context of people's lives directly. Mediation is carried out to help resolve local problems. The lack of help in dealing with problems is a concern, especially regarding the lack of knowledge of Christ. A personal approach is taken to introduce religious values ??to the community. The pioneering of the cell community was first carried out on January 17 2024 with members who had diverse religious backgrounds. Church growth is measured quantitatively and qualitatively, which includes growth in the number of congregations and spiritual development. The first step in forming a church is through starting a cell community, with the hope that churches can develop in the area. The online communication service is held every Monday as an effort to spread God's word, in accordance with His promise in Isaiah 55:11.